Deletion of a Putative GPI-Anchored Protein-Encoding Gene Aog185 Impedes the Growth and Nematode-Trapping Efficiency of Arthrobotrys oligospora by Disrupting Transmembrane Transport Homeostasis. (14th November 2022) - Peng, Hui; Lu, Hengqian; Dong, Xinyuan; Liang, Xiao; Sheng, Kangliang; Wang, Jingmin; Kong, Xiaowei; Zha, Xiangdong; Wang, Yongzhong
Abstract : Nematode-trapping fungus (NTF) is a crucial predator of nematodes, which can capture nematodes by developing specific trapping devices. However, there is limited understanding of the role and mechanism of cell surface proteins attached to the surface of mycelia or trapping cells. Here, the effects of a putative GPI-anchored protein-encoding gene Ao g185 on the growth and nematode-trapping efficiency of A. oligospora were investigated. Compared to the wild-type (WT) strain, the Δ Ao g185 mutant grew more slowly, exhibited a 20% decrease in conidiation, delayed conidial germination, generated fewer traps, attenuated nematode trapping efficiency, and was more sensitive to chemical stressors. Transcriptomic analysis indicated that a large number of transmembrane transport-related genes were differentially expressed between the WT and Δ Ao g185 mutant strains. Ao g185 deletion could damage the intrinsic components of the membrane and cytoskeleton. Specifically, knockout of Ao g185 disrupted transmembrane transport homeostasis during the phagocytosis, cell autophagy, and oxidative phosphorylation processes, which were associated with the fusion of cells and organelle membranes, transport of ions and substrates, and energy metabolism. Hence, the putative GPI-anchored protein-encoding gene Ao g185 may contribute to the lifestyle switch of NTF and nematode capture, and the effect of Ao g185 gene on cell transmembrane transport is considered key to this process. Our findings provide new insights into the mechanism of Ao g185 gene during the process of nematode trapping by NTF.